The morphological and physiological features of bees of grey mountain race and preservation of their genofund in Dagestan - A. R. Gasanov; A. M. Abakarova (Юг России: экология, развитие, 2015)
In Dagestan Republic morphological attributes of bees show variability depending on breadth of region and vertical zone. Researches show that hybrids inheritance of some attributes evades aside the greatest or least value of studied attribute of the parent. According to number of attributes bees of mountain zone come nearer to standards on breed.